2023
DOI: 10.3390/jmse11122222
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Fucales (Ochrophyta, Phaeophyceae) along the Coasts of Lipari and Vulcano (Aeolian Archipelago), Tyrrhenian Sea (Central Mediterranean Sea)

Giuliana Marletta,
Andrea Lombardo,
Donatella Serio
et al.

Abstract: This study explored the biodiversity of Fucales along the islands of Lipari and Vulcano, almost ten years after the last studies on the phytobenthos of these islands. To carry out this research, a monitoring activity was conducted through both scuba dives and snorkelling activities. Through this study, a total of 13 species (four belonging to Cystoseira, three to Ericaria, two to Gongolaria, and four to Sargassum) was observed. When comparing the present data with past studies, nine species were previously rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…As concerns the reproductive period, in the study areas, this species is fertile from June to August, with the maximum fertility observed in July. The reproductive period observed during this study aligns with that reported by Blanfuné et al [17] for the same species in France and Corsica, and for other Sargassum species present in Sicily [18,38].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As concerns the reproductive period, in the study areas, this species is fertile from June to August, with the maximum fertility observed in July. The reproductive period observed during this study aligns with that reported by Blanfuné et al [17] for the same species in France and Corsica, and for other Sargassum species present in Sicily [18,38].…”
Section: Discussionsupporting
confidence: 92%
“…Virgin Islands and Antilles -- [20] Venezuela -- [21] Salvage Islands -- [22] Cuba 2-4 Rocky [9,23] Brazil 1-5 Sandy [19,24,25] Trinidad and Tobago -- [26] Mexico -- [27,28] Canary Islands -- [29] Madeira -- [30] Costa Rica 0-1.5 Rocky and sandy [31] Azores -- [32] Puerto Rico Up to 17 - [33] Pacific Ocean Philippines -- [34] Mediterranean Sea Spain 12 - [16] Italy 4-28 Rocky and sandy [14,18] France and Corsica Upper and medium infralittoral - [17]…”
Section: Atlantic Oceanmentioning
confidence: 99%